Factors that facilitate consumer uptake of sustainable dietary patterns in Western countries: a scoping review - Srinivasan, Soumya; Galvez, Abby; Krieger, Rebecca; Sebo, Amy; Mckever, Maya; Nestico, Daniella; Carlsson, Liesel; Wegener, Jessica; Everitt, Tracy (Frontiers in Sustainable Food Systems, 2024)
Objectives This scoping review aims to describe factors that facilitate consumer-level transitions to more environmentally sustainable diets. Methods Using scoping review methods, four databases were searched for articles published in English examining facilitators to consuming an environmentally sustainable diet and focused on consumers, using data collected in Western countries, and were published between 2012 and 2022. Researchers extracted study characteristics and factors influencing adoption or uptake of sustainable foods or dietary patterns. Using this data, researchers conducted a thematic analysis to determine five main themes describing leverage points (modifiable) for dietary transitions. Results Results are reported per PRISMA guidelines: 21 studies were included with data from the U.K., U.S., Australia, and Europe. The results of this review indicate that values, knowledge, marketing, consumer-product relationships, and support networks, along with their respective subthemes, may be central drivers of consumer adoption of sustainable dietary patterns. Consumers are more likely to purchase and consume products which are familiar and appealing and align with their values. Cost, lack of knowledge, and lack of social support act as barriers to dietary change to more sustainable food choices. Income, education, ethnicity, sex, and employment were common individual-level characteristics identified as influential over likelihood of adopting environmentally sustainable dietary patterns. Individual-level characteristics create nuances in both likelihood to adopt, and the experience of barriers to adopting, sustainable dietary patterns. Conclusion Knowledge of leverage points and individual-level nuances is useful in informing strategies to facilitate transitions to more sustainable diets.